(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Over the last two decades there has been a proliferation of partnerships between business and government, multilateral bodies and/or social actors such as NGOs and local community organizations engaged in promoting development. While proponents hail these partnerships as an important new approach to engaging business, critics argue that they are not only generally ineffective but serve to legitimate a neo-liberal, global economic order which inhibits development. This study examine impact of partnership business on economic development and growth of Ondo state through Pay-Attitute Company by assigning questionnaire to the study. The data was analyzed using descriptive statistic in line with Chi-square Technique. Three hypotheses formulated were tested using chi-square technique at 0.05(5%) level of significance. Findings disclose that ascertain ways of solving problems through effective technique has impact on growth of partnership business in Ondo State and also, partnership business has impact on the life of Ondo state citizens as shown from the result P-value (0.000<0.05). It was evident from findings that there is the need that partners in the partnership business should be educated more on the rules of business success and business failure so that it will guide them in handling the day to day operations of their business. The research recommends that though it is not mandatory that partnership must reach an agreement by law before business commences but it is very important.